The Benefits of Google Docs Based Collaborative Writing Activities in EFL College Writing Dynamics - Kristian Florensio Wijaya (Journal of English Language Teaching, Linguistics, and Literature (JETLEE), 2026)
It is critically important for second language educationalists to equip EFL (English as a Foreign Language) learners with effective online collaborative writing platforms, enabling them to enhance writing skills and competencies through the dissemination of mutual group sharing dynamics. This small-scale literature review study aimed to investigate the benefits of Google Docs-based collaborative writing activities in EFL college writing dynamics context. Thus, the researcher employed a thematic analysis approach when analyzing the findings of 30 prior Google Docs-based collaborative writing activities to ensure the credibility, sound, and relevant results. The thematically categorized findings unveiled that Google Docs collaborative writing activities serves as a rewarding technological platform that should be further incorporated and integrated into modern EFL college writing learning process or in the curricula level, fostering second language learners’ gradual transformation into more proficient and motivated writers.